Explore BrainMass
Share

Explore BrainMass

    Partial Fraction Proof

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    See attachment.

    © BrainMass Inc. brainmass.com October 10, 2019, 6:46 am ad1c9bdddf
    https://brainmass.com/math/calculus-and-analysis/partial-fraction-proof-556474

    Attachments

    Solution Preview

    To understand the concept, you go a step back to

    P(x)/Q(x) = A(x) + R(x)/Q(x)

    As per concept of division, R(x) is a remainder of P(x) for Q(x), and therefore should have at least one degree less than degree of Q(x).

    e.g.,
    P(x) = x^4 + x^3 + x^2 + 2 x + 1 (degree = 4)
    Q(x) = x^2 + 1 ( degree = 2)

    Here, P(x) can be written in terms of Q(x) as:
    x^4 + x^3 + x^2 + 2 x + 1 = (x^4 + x^3 + x^2 + x) + (x + 1) == (x^2 + 1) * ( x^2 + x ) + (x +1)

    You can observe that (x^2 + 1) can not further decompose (x+1)

    Hence,
    (x^4 + x^3 + x^2 + 2 x + 1)/(x^2 + 1) = (x^2 + x) + (x+1)/(x^2+1)
    => P(x) = Q(x) * A(x) + R(x)
    Here,
    P(x) = x^4 + x^3 + x^2 + 2 x + 1 (degree = 4)
    Q(x) = x^2 + 1 (degree = 2)
    A(x) = x^2 + x (degree = 4 - 2 = 2 == degree(P) ...

    Solution Summary

    Some of the concepts of partial fraction are described through a few examples, to understand the concept properly.

    $2.19